Traits of Mortadella from Meat of Different Commercial Categories of Indigenous Dairy Cattle - Cristina Giosuè; Giuseppe Maniaci; Riccardo Gannuscio; Marialetizia Ponte; Marianna Pipi; Antonino Di Grigoli; Adriana Bonanno; Marco Alabiso (Animals, 2024)
The rising interest in healthier meat options prompted the exploration of alternatives to traditional pork-based products, incorporating meat from different livestock species, feeding regimens, and functional ingredients. This study investigates the production of healthier meat products by examining the physicochemical traits, fatty acid profile, and sensory properties of mortadella made with Cinisara meat of four young bulls and four adult cows, and four females of the Nebrodi Black Pig. All the animals were fed principally on natural resources. Nutritional analysis revealed different levels of moisture, protein, fat, and ash in raw materials, with pistachios contributing to a healthy fatty acid profile rich in monounsaturated and polyunsaturated fatty acids. Formulations using cow meat exhibited higher fat content and caloric value, resulting in sensory attributes such as more intense color, improved fat cube adhesion, and pronounced odors compared to young bull and control mortadella. Fatty acid analysis demonstrated distinctive profiles influenced by the meat type used and, as expected, bovine products showed higher contents of rumenic and other conjugated linoleic acids. Pork mortadella displayed greater ω6 and ω3 values, with a healthier ω6/ω3 ratio comparable to those found in cow products. Young bull mortadella showed the worse atherogenic and thrombogenic indices. The findings underscore the impact of raw materials on the nutritional and sensory attributes of mortadella, emphasizing the necessity for interventions to enhance fatty acid composition in processed meat products.